Hepatocyte autotaxin expression promotes liver fibrosis and cancer. Issue 4 (7th February 2017) - Kaffe, Eleanna; Katsifa, Aggeliki; Xylourgidis, Nikos; Ninou, Ioanna; Zannikou, Markella; Harokopos, Vaggelis; Foka, Pelagia; Dimitriadis, Alexios; Evangelou, Kostas; Moulas, Anargyros N.; Georgopoulou, Urania; Gorgoulis, Vassilis G.; et al.
Abstract : Autotaxin (ATX) is a secreted lysophospholipase D that catalyzes the production of lysophosphatidic acid (LPA), a pleiotropic growth‐factor–like lysophospholipid. Increased ATX expression has been detected in various chronic inflammatory disorders and different types of cancer; however, little is known about its role and mode of action in liver fibrosis and cancer. Here, increased ATX expression was detected in chronic liver disease (CLD) patients of different etiologies, associated with shorter overall survival. In mice, different hepatotoxic stimuli linked with the development of different forms of CLDs were shown to stimulate hepatocyte ATX expression, leading to increased LPA levels, activation of hepatic stellate cells (HSCs), and amplification of profibrotic signals. Hepatocyte‐specific, conditional genetic deletion and/or transgenic overexpression of ATX established a liver profibrotic role for ATX/LPA, whereas pharmacological ATX inhibition studies suggested ATX as a possible therapeutic target in CLDs. In addition, hepatocyte ATX ablation and the consequent deregulation of lipid homeostasis was also shown to attenuate hepatocellular carcinoma (HCC) development, thus implicating ATX/LPA in the causative link of cirrhosis and HCC. Conclusion : ATX is a novel player in the pathogenesis of liver fibrosis and cancer and a promising therapeutic target. (Hepatology 2017;65:1369‐1383).